2014
DOI: 10.1302/2046-3758.39.2000287
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic compressive loading on 3D tissue of human synovial fibroblasts upregulates prostaglandin E2 via COX-2 production without IL-1β and TNF-α

Abstract: ObjectiveExcessive mechanical stress on synovial joints causes osteoarthritis (OA) and results in the production of prostaglandin E2 (PGE2), a key molecule in arthritis, by synovial fibroblasts. However, the relationship between arthritis-related molecules and mechanical stress is still unclear. The purpose of this study was to examine the synovial fibroblast response to cyclic mechanical stress using an in vitro osteoarthritis model.MethodHuman synovial fibroblasts were cultured on collagen scaffolds to produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 59 publications
5
31
0
Order By: Relevance
“…Our results indicate that short-term high-frequency cyclic tensile strain induced a mechanical stress response, as a significant increase in the inflammatory and innate immune response activating marker IL-6 could be detected. This concurs with previous findings applying pressure on fibroblasts [24,48]. Interestingly, the application of the dynamic stretching protocol had beneficial effects on IL-6 expression in synovial fibroblasts, contrary to chondrocytes [23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results indicate that short-term high-frequency cyclic tensile strain induced a mechanical stress response, as a significant increase in the inflammatory and innate immune response activating marker IL-6 could be detected. This concurs with previous findings applying pressure on fibroblasts [24,48]. Interestingly, the application of the dynamic stretching protocol had beneficial effects on IL-6 expression in synovial fibroblasts, contrary to chondrocytes [23].…”
Section: Discussionsupporting
confidence: 92%
“…In general, in vitro experiments suffer from inadequate simulation of in vivo situations, especially when mimicking movement and the effect of mechanical strain on cells. For this reason, various protocols and applications are published aiming to overcome this issue [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, exogenously added TNF-α and IL-1β stimulated CGRP expression in vitro, but no significant correlation was detected between TNF-α- or IL-1β-induced CGRP mRNA expression levels in the synovial tissue from knee joints of OA patients. In a recent study, Nakata et al [ 21 ] demonstrated that cyclic compressive loading on a 3D-cultured construct of human synovial fibroblasts upregulates PGE2 and COX-2 in the absence of IL-1β or TNF-α stimulation. These results suggest that CGRP may be regulated by PGE2 in an IL-1β- and TNF-α-independent manner in the synovium of OA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the physiological role of COX-1 in the body's normal metabolism and protection by the release of prostaglandin, while COX-2 has been recognized as an inducible or pathological enzyme that can be induced by various chemical/physical injuries or biological factors. COX-2 also participates in the inflammatory response by facilitating prostaglandin synthesis (Lee et al, 2014b;Shimomura et al, 2014). The pathogenesis of OA or RA is not well-understood, although abnormal expression of certain genes or proteins has been found to be correlated with the occurrence of these diseases to some degree.…”
Section: Introductionmentioning
confidence: 99%